The Influence of Intermittent Fasting on Selected Human Anthropometric Parameters - Čermáková, Erika; Forejt, Martin; Čermák, Martin (International journal of medical sciences, 2024)
Background: Intermittent fasting may be an effective tool for weight loss, but it is still unclear from previous studies to date whether it is as effective as a continuous energy restriction in terms of reducing adipose tissue and whether it leads to unwanted muscle loss. Objectives: The aim of this study was to compare the effect of intermittent fasting (IF) with continuous energy restriction (CER) on the body weight and body composition and to assess the effect of intermittent fasting also in isolation from the energy restriction. Methods: After completion of a three-week dietary intervention, differences in the weight loss and differences in the body composition were compared between three groups. The first group consumed 75% of their calculated energy intake requirements in a six-hour time window. The second group consumed 75% of their calculated energy intake requirements without a time window and the third group consumed 100% of their calculated energy intake requirements in a six-hour time window. The changes in the weight and body composition were assessed by BIA. Results: Of the 95 randomized participants, 75 completed the intervention phase of the study. The highest mean weight loss was achieved by the IF with ER (energy restriction) group (2.3 ± 1.4 kg), followed by the CER group (2.2 ± 1.1 kg); the difference between the groups did not reach statistical significance. The lowest mean weight loss was observed in the IF without ER group (1.1 ± 1.2 kg), the difference reaching statistical significance compared to the IF with ER (p=0.003) and CER (p=0.012) groups. The highest mean adipose tissue loss was observed in the CER group (1.5 ± 1.2 kg) followed by the IF with ER group (1.3 ± 1.1 kg), with no statistically significant differences between the groups. A mean adipose tissue loss was found in the IF without ER group (0.9 ± 1.1 kg) with no statistically significant differences compared to the IF with ER and CER groups. The highest mean fat-free mass loss was found in the IF with ER group (1.1 ± 1.0 kg), followed by the CER group (0.65 ± 0.91 kg) with no statistically significant differences. The IF without ER group showed the lowest mean fat-free mass loss (0.2 ± 1.3 kg), which reached statistical significance compared to the IF with ER group (p=0.027). Conclusion: The results showed a comparable effect in the weight loss and body fat reduction regardless of the timing of the food intake. The diet quality, together with the energy intake, appeared to be one of the most important factors influencing the body composition.
Keywords: Anthropometry; skeletal muscle mass; lidé; Middle Aged; Adult; Body Composition; Obesity; Intermittent Fasting; Female; Energy Intake; Body Mass Index; antropometrie; Humans; složení těla; Fasting; index tělesné hmotnosti; obezita; energetický příjem; kalorická restrikce; tuková tkáň; přerušované hladovění; lidé středního věku; mužské pohlaví; mladý dospělý; hmotnostní úbytek; Adipose Tissue; omezení příjmu potravy; Weight Loss; ženské pohlaví; Caloric Restriction; Young Adult; intermittent fasting; time-restricted feeding; body fat mass; Male; tělesná hmotnost; energy restriction; dospělí; Body Weight; visceral fat